The Influence of Company Size, Intergovernmental Revenue, and Leverage on Financial Performance: A Case Study of Regency Governments in West Java Province - Putri, Nenden Dinah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine the influence of company size, intergovernmental revenue, and leverage on the financial performance of regency governments in West Java Province. A quantitative research approach was employed, utilizing descriptive analysis and panel data regression techniques. The study is based on secondary data drawn from the APBD (Regional Budget) financial reports and the balance sheets of local governments in West Java for the period 2019–2023. The analysis results indicate that company size, intergovernmental revenue, and leverage do not significantly affect financial performance. A larger company size does not necessarily lead to improved financial performance; rather, the effectiveness of budget management and fiscal policy plays a more pivotal role. Dependence on central government transfers does not always yield positive outcomes and may reduce regional incentives to enhance locally-generated revenue (PAD). Meanwhile, leverage demonstrates a positive correlation with financial performance, but its impact is statistically insignificant, suggesting that the effectiveness of debt utilization and fiscal strategy is more crucial in ensuring regional financial stability.